2019
DOI: 10.5005/jp-journals-10024-2489
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibacterial and Antifungal Properties and In Vivo Cytotoxicity of Peruvian Passiflora mollisima

Abstract: Aim:The antimicrobial activity of Passiflora mollissima is largely due to its aliphatic and aromatic hydrocarbons, terpenes, alkaloids, ketones, esters, alcohols, and lactones. The objective of this research was to evaluate the antimicrobial activity of the compounds in the Passiflora mollissima (Tumbo) fruit and leaves included also on cultured strains of the microorganisms Streptococcus mutans, Streptococcus oralis, Streptococcus sanguinis and Candida albicans.Materials and methods: Antimicrobial activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
(28 reference statements)
0
16
0
1
Order By: Relevance
“…Multiple studies have demonstrated its important medicinal properties. However, its antibacterial effectiveness against S. mutans , which has shown a relevant role in the pathogenesis of different oral diseases, has not yet been demonstrated [ 3 5 ]. Tooth decay is one of the most prevalent diseases in Peru, and it is associated with different etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated its important medicinal properties. However, its antibacterial effectiveness against S. mutans , which has shown a relevant role in the pathogenesis of different oral diseases, has not yet been demonstrated [ 3 5 ]. Tooth decay is one of the most prevalent diseases in Peru, and it is associated with different etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Direct observation was made, and the measurement of the inhibitory halo (Kirby–Bauer method)[ 6 8 9 10 ] of four concentrations at 25%, 50%, 75%, and 100% of the EOC and nystatin on strains of Candida albicans ATCC 10231 was taken; the data obtained was recorded in a data collection sheet where the inhibition halos measurements in millimeters, formed in each of the discs embedded with the EOC. In the period of 24 and 48h of having made the sowing, the readings and filling of the collection sheet were made, taking into account the identification of the sample, identification of the concentration used, and the measurement in millimeters of the halo of inhibition formed [ Figure 2 ].…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…It also refers to the intervention to recover health through the use of herbs with medicinal properties or their derivatives. [ 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the use of natural products as a new antimicrobial alternative,[ 8 9 10 11 ] and have described the importance of the application of substances such as intraconduction medication in pieces with asymptomatic apical periodontitis to eliminate existing bacteria, and also to achieve successful duct treatment.…”
Section: Introductionmentioning
confidence: 99%